2007
DOI: 10.1007/s00018-007-7008-z
|View full text |Cite
|
Sign up to set email alerts
|

What tangled webs they weave: Rho-GTPase control of angiogenesis

Abstract: The members of the Rho family of small GTPases are involved in an array of cellular processes, including regulation of the actin cytoskeleton, cell polarity, microtubule dynamics, membrane transport, and transcription factor activity. Recent findings have implicated the Rho-proteins as key regulators of angiogenesis, modulating a diversity of cellular processes, including vascular permeability, extracellular matrix remodeling, migration, proliferation, morphogenesis, and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
135
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(140 citation statements)
references
References 112 publications
3
135
0
2
Order By: Relevance
“…In this regard, it has been reported that the RhoA, Rac1, and Cdc42 small GTPases, key regulators of actin cytoskeleton dynamics, play a major role in vascular processes such as endothelial cell motility, angiogenesis, and endothelial cell permeability (30). When we investigated the activation of these GTPases by ANGPTL4, we found an induction of RhoA and Cdc42 activity in treated endothelial cells (Fig.…”
Section: Vegf Is Not Sufficient For the Exudative Phenotype In Vgpcr mentioning
confidence: 62%
“…In this regard, it has been reported that the RhoA, Rac1, and Cdc42 small GTPases, key regulators of actin cytoskeleton dynamics, play a major role in vascular processes such as endothelial cell motility, angiogenesis, and endothelial cell permeability (30). When we investigated the activation of these GTPases by ANGPTL4, we found an induction of RhoA and Cdc42 activity in treated endothelial cells (Fig.…”
Section: Vegf Is Not Sufficient For the Exudative Phenotype In Vgpcr mentioning
confidence: 62%
“…These molecules may recruit Par-3 to the SC-axon interface, resulting in asymmetric localization and cytoskeletal reorganization by regulating actin and microtubule dynamics. Par-3 can regulate the Rho-family GTPases through GEFs (guanine nucleotide exchange factors) to mediate actin reorganization and possibly control axonal sorting and the unidirectional ensheathment of the axon (Benninger et al, 2007;Bryan and D'Amore, 2007;Nodari et al, 2007). Additionally, during asymmetric cell division, Par-3 recruits proteins such as Inscuteable, which in turn recruits Partner of Inscuteable (Pins) (Cai et al, 2003;Siller et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Candidates for such regulatory roles include members of the Rho-GTPase family of molecules, such as Rho and Rac1, which translate external signals into alterations in cytoskeletal reorganization and hence have the ability to influence migration. A large body of literature has characterized the cellular mechanisms and signal transduction pathways of Rho, Rho-dependent kinase (ROCK) and related regulatory members, such as Rac and PI3K, on cellular motility and chemotaxis in various cell types [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%